Advances in prevention of RSV disease in infants - Prof Heather J Zar (International Journal of Infectious Diseases)
Introduction: Respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infection (LRTI), hospitalisation and mortality in infants and young children globally. The greatest burden is in low-and–middle income countries (LMICs), with the highest rates of RSV-hospitalisation in infants under 3 months old. Preterm infants, children with chronic lung disease of prematurity, Down's syndrome, congenital heart disease, or immunodeficiency also have a higher risk of severe disease. . A RSV pre-fusion (F) maternal vaccine and long-acting monoclonal antibody (nirsevimab) have been licensed for prevention of RSV disease in infants and young children in several high income countries. Methods: Review of the published literature including efficacy and effectiveness studies of maternal vaccination given to pregnant women or nirsevimab given to infants. Results: Maternal RSV vaccine given at 24-36 weeks of pregnancy was effective for prevention of medically attended RSV-LRTI and severe RSV-LRTI through 6 months after birth in a phase 3 study (MATISSE) conducted in 18 countries over 2 RSV seasons. Vaccination was safe with no significant difference in adverse events between infants born to mothers who received RSV-preF vaccine compared to placebo, although a numerical imbalance in preterm births occurred. This was predominantly in 2 middle income countries (Argentina and South Africa), unrelated to vaccine timing or gestational age at vaccination. Most were late preterm births and there was no associated mortality; these also occurred at specific time periods coinciding with the COVID-19 delta or omicron waves. Nirsevimab, given as a single dose (50mg in infants <5kg; 100mg in those >5kg), prior to or during the RSV season had high efficacy in preventing RSV-LRTI hospitalization and severe RTSV-LRTI in preterm and in full-term infants, as well as in young children with underlying conditions through 150 days post administration in phase 2 and 3 trials. High effectiveness for nirsevimab against RSV-hospitalisation or severe disease as well as for all-cause LRTI in infants and in at-risk children up to 2 years of age has also been reported in several countries post implementation. Discussion: Either of these interventions have high efficacy particularly for preventing severe RSV-LRTI in clinical trials, and each have been recommended by the World Health Organisation. Uptake has been rapid in high income countries, but is very limited implementation in LMICs. Decisions about implementation of maternal vaccine or nirsevimab in national programs will need to consider feasibility in health systems, acceptability, cost and availability of a product and RSV seasonality. Conclusion: RSV has become a preventable disease in infants and young children. Although rapid implementation has occurred in many high income countries, access remains very limited in LMICs. Access to such RSV preventive interventions are urgently needed for all children especially in LMICs.